If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+1)-3(x-6)=27
We move all terms to the left:
4(x+1)-3(x-6)-(27)=0
We multiply parentheses
4x-3x+4+18-27=0
We add all the numbers together, and all the variables
x-5=0
We move all terms containing x to the left, all other terms to the right
x=5
| -6x+3=-9-2x | | -x+2=2x—1 | | 6x/3=27 | | p5=-4 | | 6x-23=8x-13 | | 2(v-1)-4=(2v-3) | | x/3=x/9+3 | | 2(3x+1)=x*8 | | –2a–3+17a=16a+11 | | 3u-36=-2(u+8) | | 6x+5=5x+35 | | -25+5n=2n+24 | | -4x+-11=13 | | F(x)=(14-2x)(8.5-2x)(x) | | –5v=–4v+8 | | -(7y+0.6)=3.6–y | | -4x+-11=1 | | 3.85b-0.415=8.44 | | -3(3+x)+4(x-6-)=-4 | | -4(3t-5)+8t=3t-2 | | -5(k+6)+7(k-4)= | | 10x+4=6x-15 | | 5x+30=180-30 | | 8(x*2)=2x+16 | | 7x–19=10+8x | | 59-u=168 | | t(10)=20t(15)=50 | | 7(-5+x)=-28 | | 51=3(3m+2 | | -8-6x=4-2(2x-5) | | -7y-49=-2(y+2) | | 4m-4=8m+20 |